Study protocol for TILDA COVID-19 survey. Altered lives in a time of crisis: preparing for recovery from the impact of the COVID-19 pandemic on the lives of older adults - Ward, Mark; Clarke, Niamh; Wang, Minjuan; McGarrigle, Christine A; De Looze, Céline; O’Halloran, Aisling M; Kenny, Rose Anne (My University, 2021)
Background: Older adults are the most at-risk of contracting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and among the most affected by measures put in place to prevent the spread of the virus. While the full effect of the public health measures, such as social distancing and wearing masks in public spaces, implemented since March 2020 are not yet known, it is expected that they will have a severely damaging effect on physical and psychological wellbeing. The Irish Longitudinal Study on Ageing (TILDA) has been researching the lives of older adults in Ireland since 2008 with data collection conducted at two-year intervals. With an established research infrastructure, TILDA was ideally placed to examine the effect of the coronavirus disease 2019 (COVID-19) pandemic on older adults. The aim of this study is to document the lives of older adults during the COVID-19 pandemic to understand the effect of the pandemic and public health responses on their wellbeing. Methods: Data was collected from TILDA participants via self-completion-questionnaire (SCQ). The SCQ contains ten sections that capture information on many aspects of people’s lives during the pandemic including, changes in behaviour and social interactions, physical and psychological wellbeing indicators, healthcare utilisation, and exposure to SARS-CoV-2. Ethical approval was granted by the National Research Ethics Committee (NREC). Conclusions: Research findings will be shared in a variety of formats including research reports and briefs, presentations, and academic papers. Data will be archived in the Irish Social Science Data Archive (ISSDA) and the Inter-university Consortium for Political and Social Research (ICPSR). As well as documenting the impact of the COVID-19 pandemic on older adults, findings from this study will provide important information to policy-makers as we respond to the damage caused by the COVID-19 pandemic.
PUBLISHED
Keywords: COVID-19; SARS-CoV-2; Older adults; Ageing; TILDA; Public health; Social gerontology; Survey methodology; Ageing; Health; Third age/ageing